Trust the Capitonnage in the Giant Cyst: Case Report - Oncel, Murat; Yildiran, Huseyin; Sunam, Guven Sadi (The Surgery Journal, 2018)
Cyst hydatid in the lung is still a health problem for many countries. It develops in the lung and can grow into the lung parenchyma. When it is diagnosed as a giant cyst, surgery should be performed. In the surgery, capitonnage is necessary to protect the lung parenchyma.
Keywords: giant cyst hydatid; lung; surgery